Macrophage P2X7 Receptor Function Is Reduced during Schistosomiasis: Putative Role of TGF-β1 - Oliveira, Suellen D’arc Santos; Nanini, Hayandra Ferreira; Savio, Luiz Eduardo Baggio; Waghabi, Mariana Caldas; Silva, Claudia Lucia Martins; Coutinho-Silva, Robson (Mediators of Inflammation, 2014)
Schistosomiasis is a chronic inflammatory disease whose macrophages are involved in immunopathology modulation. Although P2X7 receptor signaling plays an important role in inflammatory responses mediated by macrophages, no reports have examined the role of P2X7 receptors in macrophage function during schistosomiasis. Thus, we evaluated P2X7 receptor function in peritoneal macrophages during schistosomiasis using an ATP-induced permeabilization assay and measurements of the intracellular Ca2+ concentration. ATP treatment induced significantly less permeabilization in macrophages from S. mansoni-infected mice than in control cells from uninfected animals. Furthermore, P2X7-mediated increases in intracellular Ca2+ levels were also reduced in macrophages from infected mice. TGF-β1 levels were increased in the peritoneal cavity of infected animals, and pretreatment of control macrophages with TGF-β1 reduced ATP-induced permeabilization, mimicking the effect of S. mansoni infection. Western blot and qRT-PCR data showed no difference in P2X7 protein and mRNA between uninfected, infected, and TGF-β1-treated groups. However, immunofluorescence analysis revealed reduced cell surface localization of P2X7 receptors in macrophages from infected and TGF-β1-treated mice compared to controls. Therefore, our data suggest that schistosomiasis reduces peritoneal macrophage P2X7 receptor signaling. This effect is likely due to the fact that infected mice have increased levels of TGF-β1, which reduces P2X7 receptor cell surface expression.